(untitled) (Móin-Móin - Revista de Estudos sobre Teatro de Formas Animadas, 2018)
This article reflects on a recurring question often in the field of professional training on puppetry: is it possible to describe the content and form of making art in our art, and communicate through usual process of teaching and learning? How the experienced artist, in his role of teacher, with the student or trainee is linked? Keywords: Transmigrate. Emptying. Póiesis-tekné. Manipulation-interpretation.